The inspiration of corporate internet reporting: the perspective of Malaysian corporations - Turmin, Siti Zaidah; Osman, Mohamad Noor Hisham (UTHM Press, 2017)
Corporate Internet Reporting (CIR) is the communication process between corporations and stakeholders via the Internet medium. The use of CIR by corporations is considered as a precondition for success, as it offers the facility to provide stakeholders with information to make well-informed and timely investment decisions. This study examines the reasons that motivate Malaysian listed corporations to practice CIR. The study was conducted on 310 publicly listed Malaysian corporations across eleven various economic sectors. In gathering the data, a questionnaire survey was distributed to the preparers of CIR who are represented by the chief financial officers, accountants, finance managers or investor relations managers of the companies. The data were analyzed using descriptive statistics and the independent sample t-test. The results revealed that corporations’ acceptance of CIR as a norm in today’s business world was the most important reason to inspire companies to practice CIR. In addition, the timeliness, high quality, downloadable and processable format of information presented, the aspiration of companies to be in line with technological developments, increased demand for CIR by stakeholders and the ability of CIR to reach a broader range of stakeholders in disseminating corporate information were other important reasons that inspired Malaysian corporations to practice CIR. On the other hand, the study found competitive pressure and directors’ desire as trivial reasons in inspiring companies to practice CIR. Finally, the study contributes to the knowledge pertaining to CIR in Malaysia and might be useful as a reference for other developing countries in clarifying the nature of financial reporting problems.